P1_1 Could Bruce Willis Save the World? - Brown, Gregory; Hall, Ben; Back, Ashley; Turner, Stuart (Physics Special Topics, 2011)
The film Armageddon (1998) puts forward the possibility of using a nuclear weapon buried deep within an Earth-bound asteroid to split the asteroid in two, each half clearing opposite sides of the Earth with only relatively minor damage. This article investigates the feasibility of such a plan and shows that even using the largest nuclear weapon made to date, the bomb comes over 9 orders of magnitude short of the yield required.